Overcoming barriers in it education: academic and social challenges in India and Kazakhstan - O.V. Kirichok; N.A. Amankeldi; R.S. Parmanova; N.V. Doohan (Хабаршысы. Экономика сериясы)
This study examines the underlying factors contributing to IT student dropouts in India and Kazakhstan, with a focus on academic, economic, and social challenges. Employing a mixed-methods approach—quantitative analysis using SPSS and qualitative interviews—the research identifies insufficient academic readiness, financial constraints, and limited social support as primary predictors of student attrition. While both countries face similar issues, their manifestation is shaped by contextual differences: in India, disparities in infrastructure and instructional quality significantly affect access to IT education, whereas in Kazakhstan, rural-urban divides and entrenched gender norms further hinder student retention. The findings underscore the need for targeted interventions, including scholarship programs for underrepresented groups, investment in educational infrastructure, and community engagement strategies. Additionally, integrating flexible online curricula and orientation programs can enhance student support systems. This study offers practical insights for policymakers and educational institutions aiming to improve retention and foster inclusive participation in IT education across diverse student populations.